Pemetaan dan Kesesuaian Lahan Tanaman Pangan di DAS Krueng Pasee Kabupaten Aceh Utara - Samsul Suparno; Halim Akbar; Muhammad Rafli (Faculty of Agriculture, Universitas Malikussaleh, 2017)
Mapping using Geographic Information System (GIS) in food crops is an efficient and effective way to know land characteristics and their development potential in determining land suitability class in a region. This study aims to investigate the suitability class of food crops in the Krueng Pase River Basin (DAS) of North Aceh Regency, which starts from December 2016 until March 2017. The method used in this study is a survey method consisting of the preparation stage, survey introduction, main survey, data analysis and presentation of results. Some soil properties that affect land suitability classes for food crops are soil texture, cation exchange capacity (CEC), pH, basic saturation (KB), C-organic, Nitrogen, Phosphorus and Potassium. The results showed that the land suitability class for rainfed lowland rice on SPL 29, SPL 30 and SPL 31 was marginal (S3) with drainage limiting factor, phosphorus, potassium, slope and erosion hazard. Unsuitable land suitability class (N) with slope limiting factor and erosion hazard is found in SPL 26. The soil suitability class for corn and soybean is marginal (S3) with texture limiting factor, C-organic, phosphorus, potassium, slope and hazard (SP), SPL 17, SPL 18, SPL 20, SPL 21, SPL 22 and SPL 23. While the land suitability class is not suitable (N) with slope limiting factor and erosion hazard is found in SPL 15. The suggested soil conservation techniques are drainage drainage, organic and inorganic fertilizer application combined, and the making of guludan terraces